Acquired Immune Deficiency Syndrome (AIDS) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Central nervous system involvement is reported in 61 of 68 infants and children with asymptomatic AIDS (13 with ARC-AIDS-related complex) followed for 1 to 48 months (average, 18 mos) in the Depts of Neurology and Pediatrics at SUNY, Stony Brook, NY.